PENGARUH AL-QAWAID AL-USULIYYAHDAN FIQHIYYAH TERHADAP PERBEDAAN PENDAPAT DALAM FIKIH (Studi Tentang Riba Dan Bank Syari’ah) - Bachri, Ahmad Syamsul (Et-Tijarie, 2018)
The development of the times allows for new things that cannot be found at the time of the Prophet Muhammad, such as banking. Islamic banking is present as a polemic solution, because it brings Islamic missions to achieve falah (welfare). The principles used by Islamic banks, such as profit and loss sharing, economic value of time and the goal h goal. It has been clear that the usury law is haram, but if usury is associated with current banking activities, there are those who equate it with bank interest and there are differences. This is caused by the legal excavations that are used, such as those based on the rules of usul and fiqh. Both are as tools and roots in the establishment of laws, especially for today, in practice muamalah continues to experience significant developments and changes. It would be very necessary for the work of qawa 'id al us} uliyah and fiqh in response to the evolving practice of muamalah. Determination of law that starts from the rules of ushul and its jurisprudence will produce clarity in its legal products, as well as being the solution in the practices / cases of the latest muamalah, because in it will be explored in the roots and substance of the current case / practice.